Low‐Voltage Magnetoelectric Coupling in Fe0.5Rh0.5/0.68PbMg1/3Nb2/3O3‐0.32PbTiO3 Thin‐Film Heterostructures. (9th July 2021) - Zhao, Wenbo; Kim, Jieun; Huang, Xiaoxi; Zhang, Lei; Pesquera, David; Velarde, Gabriel A. P.; Gosavi, Tanay; Lin, Chia‐Ching; Nikonov, Dmitri E.; Li, Hai; Young, Ian A.; Ramesh, Ramamoorthy; et al.
Abstract: The rapid development of computing applications demands novel low‐energy consumption devices for information processing. Among various candidates, magnetoelectric heterostructures hold promise for meeting the required voltage and power goals. Here, a route to low‐voltage control of magnetism in 30 nm Fe0.5 Rh0.5 /100 nm 0.68PbMg1/3 Nb2/3 O3 ‐0.32PbTiO3 (PMN‐PT) heterostructures is demonstrated wherein the magnetoelectric coupling is achieved via strain‐induced changes in the Fe0.5 Rh0.5 mediated by voltages applied to the PMN‐PT. We describe approaches to achieve high‐quality, epitaxial growth of Fe0.5 Rh0.5 on the PMN‐PT films and, a methodology to probe and quantify magnetoelectric coupling in small thin‐film devices via studies of the anomalous Hall effect. By comparing the spin‐flop field change induced by temperature and external voltage, the magnetoelectric coupling coefficient is estimated to reach ≈7 × 10 −8  s m −1 at 325 K while applying a −0.75 V bias. Abstract : A route to low‐voltage control of magnetism in 30 nm Fe0.5 Rh0.5 /100 nm 0.68PbMg1/3 Nb2/3 O3 ‐0.32PbTiO3 heterostructures is demonstrated by inserting a MgO layer. Using the anomalous Hall effects, the magnetoelectric coupling coefficient is estimated to reach ∼7.08 × 10 –8  s m –1 at 325 K while applying a ‐0.75 V bias.